Molecular identification of mother trees of four matoa cultivars (Pometia pinnata Forst & Forst) from Pekanbaru City, Indonesia using RAPD markers - ZULFAHMI ZULFAHMI; SUCI AMALIA PERTIWI; ROSMAINA ROSMAINA; RITA ELFIANIS; ZIYAYEVA GULNAR; TULEUBAYEV ZHAXYBAY; MOMBAYEVA BEKZAT; GULSHAT ZHAPARKULOVA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Zulfahmi, Pertiwi SA, Rosmaina, Elfianis R, Gulnar Z, Zhaxybay T, Bekzat M, Zhaparkulova G. 2023. Molecular identification of mother trees of four matoa cultivars (Pometia pinnata Forst & Forst) from Pekanbaru City, Indonesia using RAPD markers. Biodiversitas 24: 1524-1530. Pekanbaru city has four matoa (Pometia pinnata Forst & Forst) cultivars, i.e. red matoa, yellow matoa, green matoa, and black matoa, but the knowledge of the genetic variation among matoa cultivars is not available. The objective of this study was to assess the genetic variation among matoa cultivars using Random amplified polymorphism DNA (RAPD) markers and to identify the specific marker to distinguish among matoa cultivars. Eighteen primers were initially screened and four matoa cultivars were analyzed with twelve primers using the RAPD marker. The results of this study found that the twelve selected RAPD primers generated 39 fragments, with fragment sizes ranging from 200 to 1500 bp. The percentage of fragment polymorphic was 80.41%, indicating the high genetic variation of the matoa cultivar. The high genetic variation of matoa in this study is caused by cross-pollinated among matoa cultivars in the field. Eleven primers can differentiate four matoa cultivars with specific bands. The obtaining unique bands can be utilized by breeders and farmers as a basis to select the parents for the genetic improvement of Matoa, cultivars or clones protection, detection of seedling purity in a nursery, and to verify the originality of the seedlings that will be cultivated.